Bone marrow adipocytes alteration in an in vitro model of Gaucher Disease - Crivaro, Andrea Natalia (2023)
Gaucher disease (GD) is caused by biallelic pathogenic variants in GBA1 gene that encodes the lysosomal enzyme glucocerebrosidase. Up to now, specific treatment for GD cannot completely reverse bone complications. Bone is composed of different cell types; including osteoblasts, osteocytes and osteoclasts. Osteoblasts are present on bone surfaces and are derived from local mesenchymal stem cells (MSCs). Depending on environment conditions, MSCs could differentiate into osteoblasts and adipocytes. Mature adipocytes-secreted adipokines and free fatty acids affect both osteoblasts and osteoclasts formation/activity and therefore mediate skeletal homeostasis. The aim of this study was to evaluate possible alterations in GD adipocyte (GD Ad) that could contribute to bone complications. MSCs were grown in adipogenic media in order to evaluate expression of differentiation markers as PPAR-γ. PPAR-γ was observed into the nucleus of GD Ad, indicating that these cells are properly stimulated. However, these cells accumulate lesser lipid droplets (LDs) than Control Ad. In order to study lipid droplet metabolism, we evaluated the lipolysis of these structures by the measurement of free glycerol in culture supernatant. Our results indicated that GD Ad had an alteration in this process, evidenced by an increase in glycerol release. We have also evaluated two enzymes involved in LDs synthesis: fatty acid synthase (FASN) and stearoyl-coenzyme A desaturase 1 (SCD1). The transcription of these genes was decreased in GD Ad, suggesting a dysfunction in the synthesis of LDs. In conclusion, our results show an alteration in LDs metabolism of GD Ad, independent of adipocyte differentiation process. This alteration would be caused by an increase in lipolysis in early stages of differentiation and also by a reduction of lipid synthesis, which could contribute with the skeletal imbalance in GD.